Draʿ Abu El-Naga, Ägypten. Deir el-Bachît und das thebanische Pauloskloster. Sakraltopographie einer Klosterlandschaft und ihre Entwicklung auf dem Hügel von Draʿ Abu el-Naga/Oberägypten. Die Arbeiten des Jahres 2018 und Frühjahres 2019 - Eichner, Ina (e-Forschungsberichte des DAI, 2019)
During excavation campaigns in the years 2018 and 2019, again questions concerning the hierarchical structures within the monastery‘s community were pursued. For the clarification of these questions, the monks‘ cells and the graves in the monastery‘s cemetery are particularly relevant features. Excavations in the dormitory building U2 on the southern terrace focused on the archaeological investigation of a room that was preserved 4 meters high. On the upper floor there was a monk‘s cell with at least three beds. In the necropolis it could be proven that the skeletonized individuals in the northern area were originally also mummified. Only here the buried individuals are in a worse state of preservation than the mummies on the south side.